2011
DOI: 10.1073/pnas.1108455108
|View full text |Cite
|
Sign up to set email alerts
|

Unique carbohydrate–carbohydrate interactions are required for high affinity binding between FcγRIII and antibodies lacking core fucose

Abstract: Antibody-mediated cellular cytotoxicity (ADCC), a key immune effector mechanism, relies on the binding of antigen-antibody complexes to Fcγ receptors expressed on immune cells. Antibodies lacking core fucosylation show a large increase in affinity for FcγRIIIa leading to an improved receptor-mediated effector function. Although afucosylated IgGs exist naturally, a next generation of recombinant therapeutic, glycoenginereed antibodies is currently being developed to exploit this finding. In this study, the crys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

30
702
2
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 679 publications
(735 citation statements)
references
References 37 publications
30
702
2
1
Order By: Relevance
“…Furthermore, fucosylation levels of the antibody have an impact on the binding to FcγRIIIa and FcγRIIIb, whereas no differences in binding were measured on any of the other Fc receptors. These results are in agreement with the literature 13, 16, 17, 18, 19. None of the cited references studied the effect of DG on fraction bound at neutral pH, and we have demonstrated that there is a significant impact.…”
Section: Discussionsupporting
confidence: 93%
“…Furthermore, fucosylation levels of the antibody have an impact on the binding to FcγRIIIa and FcγRIIIb, whereas no differences in binding were measured on any of the other Fc receptors. These results are in agreement with the literature 13, 16, 17, 18, 19. None of the cited references studied the effect of DG on fraction bound at neutral pH, and we have demonstrated that there is a significant impact.…”
Section: Discussionsupporting
confidence: 93%
“…2011), and the complete structure of a murine immunoglobulin (1IGT) used either as a protein template (Harris et al. 1997) to drive the 3D modeling or to extract its Fc portion for building one of our chimera models.…”
Section: Resultsmentioning
confidence: 99%
“…2011). Furthermore, we noticed that Chimera 1A and Chimera 1B share very similar features from a structural point of view after their energy minimization (the static rmsd between the two chimera backbones was about 2 Å with both glycosylation ladders alternatively retained from 1IGT or 3SGJ), whereas the main differences were observed in their comparison with Chimera 2 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…showed that a unique kind of carbohydrate–carbohydrate interaction coupled with increased number of newly formed hydrogen bonds and van der Waals contacts likely contribute to the increased binding affinity observed between afucosylated Fc and the Asn162-glycosylated receptor 64 . However, in the crystal structure of fucosylated Fc in complex with FcγRIIIa, the core fucose is oriented toward the second GlcNAc of the N -glycan attached to Asn162 and has to accommodate in the interface between the interacting glycan chains 64 . As a result, the whole oligosaccharide unit on Asn162 moves away from the Fc glycan, which leads to a weakened FcγRIIIa-IgG interaction.…”
Section: Molecular Mechanisms To Account For the Enhanced Affinity Ofmentioning
confidence: 99%